ANALYSIS OF FACTORS INFLUENCING BLOOD PRESSURE IN ELDERLY POSYANDU PARTICIPANTS IN NGANJUK DISTRICT - Henny Purwandari (Journal of Health, Sport, and Nursing, 2025)
Background: Hypertension is one of the major health problems in the elderly and can increase the risk of cardiovascular disease. Identification of factors that affect blood pressure in the elderly is important to support prevention and control efforts Objective: this research aims to determine the factors that influence blood pressure in elderly Posyandu participants in Nganjuk Regency, East Java. Methods: This study used a descriptive analytical design with a cross-sectional approach. The sample consisted of 78 elderly and pre-elderly people who were registered as active participants of the integrated health post in 2024. Blood pressure data were obtained from the documentation of the integrated health post for 3 months, and other variables were collected through secondary data. Data analysis was carried out using the Pearson correlation test and ordinal logistic regression with the help of Stata 17 software. Results: Most respondents (56.41%) were in the hypertension category. The results of the correlation test showed that only the variable of active participation in Posyandu was significantly related to blood pressure (r = -0.225; p = 0.047). The results of ordinal logistic regression showed that active participation in Posyandu was a significant protective factor against high blood pressure (OR = 0.239; p = 0.031). Other variables such as age, gender, waist circumference, and exercise habits did not have a significant effect (p > 0.05). Conclusion: Active participation in Posyandu has a significant relationship with more controlled blood pressure in the elderly. Strengthening the role of Posyandu in hypertension control programs in the community is needed. Keywords: blood pressure, elderly, Posyandu, hypertension, risk factors.